PENYULUHAN DAN FOLLOW-UP BAHAYA VARIAN OMICRON UNTUK MENCEGAH PENYEBARAN COVID-19 DAERAH MALANG DI SMK PGRI SINGOSARI - Faisal Muhaidin; Nur Cahyono; Primadya Anantyarta (JPM PAMBUDI, 2022)
Covid-19 is a virus that causes a pandemic throughout the world, including in Indonesia. This virus develops rapidly and mutates into various variants, one of which is the Omicron variant. This virus causes various kinds of effects. The way to break the chain of spread of the Covid-19 virus is to implement health protocols. This community service has the aim of providing counseling and follow-up on the dangers of COVID-19, the Omicron variant, to prevent the spread of COVID-19 cases at SMK PGRI Singosari. This outreach activity is carried out in 3 stages, namely pre-PMBP activities, implementation of PMBP Activities, and Post-PMBP Activities (Follow-Up). In conclusion, breaking the chain of spread of COVID-19 can be done by implementing health protocols according to government recommendations and must be accompanied by a healthy lifestyle such as consuming a balanced nutritious diet, exercise, and adequate rest and vaccination.